DNA Barcoding Analysis and Phylogenetic Position of Endemic Lysimachia savranii Species - Emre SEVİNDİK; İsa BAŞKÖSE (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Agriculture)
In this study, DNA barcode analysis and phylogenetic position of endemic species Lysimachia savranii were determined using nrDNA ITS and cpDNA rbcL sequences. Green leaves of endemic L. savranii were brought to the laboratory and genomic DNA was isolated. ITS (ITS5A and ITS4) and rbcL (rbcLaF and rbcLaR) primers were used to perform the PCR amplifications. Using BioEdit 7.2.3 and FinchTV 1.4.0, forward and reverse sequences were checked and corrected and then blasted at NCBI. For phylogenetic analyses, different species were taken from NCBI and phylogenetic trees as well as genetic distance values were revealed. The ITS sequence length was determined to be 661 nt while the rbcL sequence length was 548 nt. In both the ITS and rbcL results, L. savranii was found to be genetically closest to the L. serpyllifolia species. In the phylogenetic analysis results, L. savranii appeared in a group with L. serpyllifolia, L. nemorum and Anagilis arvensis species. Additionally, previously studies conducted revealed that Lysimachia is a paraphyletic group and this is supported by our results.